HUBUNGAN ANTARA GAYA KEPEMIMPINAN KARISMATIK KEPALA SEKOLAH DAN KEPRIBADIAN DENGAN KEINOVATIFAN GURU - Elis Sutianah; Widodo Sunaryo; Adie E. Yusuf (JURNAL MANAJEMEN PENDIDIKAN, 2018)
The objective of this research is to analyze the correlation between The Charismatic Leadership Style and Personality with the Teachers Innovation. This research uses two independent variables, those are The Charismatic Leadership Style and Personality with the Teachers Innovation. The research was conducted at 15 states Junior High Schools at Cicurug Subdistrict Sukabumi West Java in 2017 with 130 samples selected from 193 of populations, selected by Proporsional Random Sampling . This research uses survey method by analyzing data with sample and multiple correlation statistic test. The research concludes that: First, there is positive and highly significant correlation between Charismatic Leadership Style (X1) and Teachers Innovation. (Y) with regression equation ? = 49,037 + 0,603 X1 and correlation coefficient ry1 = 0,7164 and determination coefficient r2y1 = 0,5132. Second; there was positive and highly significant correlation between Personality (X2) with Teachers Innovation. with regression equation ? = 46,384 + 0,634 X2 and correlation coefficient ry2 = 0,6989 and determination coefficient r2y2 = 0,4884; and the Third, there was positive highly significant correlation between Charismatic Leadership Style (X1) and Personality (X2) all together with Teachers Innovation. (Y) with regression eqution ? = 18,872 + 0,422 ,422 ????X + 0,419 X2. , correlation coefficient ry12 = 0,8290 and r_(y.12)^2 determination coefficient 0,6873, or it means that the contribution of pedagogical competencies and achivement motivation links to Teachers Innovation. Based on the description above,teachers innovation can be enhanced through Charismatic Leadership Style and Personality.Keywords: Charismatic Leadership, Personality, Teacher Innovation